Investigation on the Properties of Concrete Containing Oil Shale Waste Ash as a Substitute for Cement - Chenglin Shi; Zijian Shi (Advances in Civil Engineering)
Oil shale waste ash (OSWA) can be divided into semicoke ash (SA), power plant ash (PPA), and grinding ash (GA), which changes the properties of binding materials in varying degrees as partial replacements of cement in cement concrete. Fluidity of cement paste test is formed to reflect the compatibility between binding materials and admixture, using the mixture of cement to test compressive strength, flexural strength, and brittleness coefficient, to determine the mixing ratio of OSWA. The optimal amount of OSWA replacing cement was optimized by orthogonal test method, and the mechanical properties and frost resistance durability tests were carried out to clarify the reasonable amount and properties of OSWA replacing cement with cement concrete. The results show that appropriate admixtures should be taken into account when OSWA is used to replace cement in order to achieve the workability of cement concrete. The brittleness coefficient and crack resistance of cement concrete can be improved by adding proper PPA and GA. The oil shale cement concrete should not be used in the parts that require high frost resistance. It is feasible to replace cement with OSWA, and the fine powder type and mixing amount can be selected according to the actual project demand.